RAZBORITOST ŽIVOTINJA - Chittick, William C.; Dubravac, Haris (Novi Muallim, 2022)
UDK 28-254 Prijevod s engleskog: Haris Dubravac Izvor: William C. Chittick, The Wisdom of Animals, “Journal of the Muhyiddin Ibn ‘Arabi Society”, Vol. 46, 2009., pp. 27–38.